1954
DOI: 10.1007/bf01340690
|View full text |Cite
|
Sign up to set email alerts
|

Isotopenbestimmung mit der Goldabsorptionsmethode

Abstract: Es wird eine schnelle und einfache Methode beschrieben die die Identifizierung yon Beta-strahlenden radioaktiven Isotopen ermOglicht. Die geringste AktivitXt die man hOCk mit dieser Methode identifizieren kaml betr~gt 50 mikro-mikro-Curie. Die Methode beruht auf den empirischen Belunden, dab die Absorption yon Beta-Spektren in Materialien yon hoher Atomnummer exponentiaI verl~uft und dab die Goldabsorptionskoeffizienten umgekehrt proportional tier 3/2-ten Potenz tier maximalen Energie der Beta-Spektra sind. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1956
1956
1961
1961

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…Furnished by National Bureau of Standards. 6 Furnished by Oak Ridge National Laboratory. Equation 2 is simple enough to allow use in high school laboratory experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furnished by National Bureau of Standards. 6 Furnished by Oak Ridge National Laboratory. Equation 2 is simple enough to allow use in high school laboratory experiments.…”
Section: Resultsmentioning
confidence: 99%
“…The absorption coefficient, l/ , has been found (6,20,25) to depend on the maximum energy of the beta spectrum, E, in the following way: X(mg./sq. cm.)…”
Section: R(c'pm) =mentioning
confidence: 99%
See 1 more Smart Citation
“…In the original work, the Gottingen group measured the absorption spectra of various alkali halides activated by small amounts of thallium (25,36,40), copper (23,135), silver (40,135), and lead (36). They studied the variation of the absorption with concentration of impurity (23,67,68) and found that, at least for low concentrations, the intensity of absorption is directly proportional to the concentration of the impurity.…”
Section: Spectral Measurementsmentioning
confidence: 99%
“…The absorption spectra of Tl-activated alkali halide phosphors (1,2) have been studied extensively and their excitation and emission spectra (3,4) have received some attention. 1 In addition an attempt has been made to calculate from first principles the absorption and emission spectrum of Tl-aetivated KC1 (5) and to correlate this ~dth experimental data, including data on thermoluminescence.…”
mentioning
confidence: 99%